1995
DOI: 10.1002/ca.980080604
|View full text |Cite
|
Sign up to set email alerts
|

Extensor tendons of the fingers: Arrangement and variations‐ii

Abstract: One hundred eighty-one dissected hands were examined to study the pattern of extensor tendons on the dorsum of the hand. Extensor digitorum often had multiple tendons for the middle and ring fingers. Its contribution to the little finger was usually by a bifurcating tendon common with that of the ring finger. The index finger always received a single tendon. Intertendinous connections between the various tendons of the extensor digitorum were variable but were most frequent between ring and middle fingers. Ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
74
3
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(97 citation statements)
references
References 6 publications
17
74
3
1
Order By: Relevance
“…Previous reports record an equal incidence of EDM between right and left forearms. 4,5 However, in this study, the EDM was prevalent on the left forearm than on the right forearm at a ratio of 5:2. Some reports indicate that a bilateral presence of EDM is a rare occurrence.…”
Section: Discussioncontrasting
confidence: 60%
See 3 more Smart Citations
“…Previous reports record an equal incidence of EDM between right and left forearms. 4,5 However, in this study, the EDM was prevalent on the left forearm than on the right forearm at a ratio of 5:2. Some reports indicate that a bilateral presence of EDM is a rare occurrence.…”
Section: Discussioncontrasting
confidence: 60%
“…Previous investigators have reported its prevalence ranging from 1% to 12% of cadavers. 2,[4][5][6][7][8]10 The current report shows the prevalence is at the middle of this range (7.4%). A higher incidence is reported by von Schroeder and Botte, 4 with a 12% prevalence of the EDM.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…el-Badawi et al reported 2 to 6 ED tendon and 3 to 8 tendons proximal & distal to the extensor retinaculum respectively [11]. In our study, the number ED tendons varied from 3 to 6 proximally and 3 to 7 distal to extensor retinaculum (ER).…”
Section: Discussionmentioning
confidence: 43%